Respuesta :

Answer:

Option 3

Step-by-step explanation:

Option 1

f(a) = a² - 4

g(a) = √a

(gof)(a) = [tex]\sqrt{a^{2}-4}[/tex]

Option 2

f(a) = [tex]\frac{1}{2}a-1[/tex]

g(a) = 2a - 2

(gof)(a) = [tex]2[\frac{1}{2}a-1]-2[/tex]

           = (a - 2) - 2

           = a - 4

Option 3

f(a) = 5 + a²

g(a) = [tex]\sqrt{(a-5)}-2[/tex]

(gof)(a) = [tex]\sqrt{(a^2+5-5)}-2[/tex]

           = |a| -2

Option 4

f(a) = 3 - 3a

g(a) = 4a - 5

(gof)(a) = 4(3 - 3a) - 5

            = 12 - 12a - 5

            = 7 - 12a

Therefore, Option 3 is the answer.

ACCESS MORE